Pengembangan Media Pembelajaran Berbasis Macromedia Flash Dengan Pendekatan Kontekstual - Rosyadi, Firmansyah Akbar; Agustin, Ririn Dwi; Yahmun, Yahmun (Postulat : Jurnal Inovasi Pendidikan Matematika, 2023)
This research was conducted at Singa Putih Prigen Featured MTs for the development of learning media for macromedia flash-based flat shapes. This study uses research and development (R&D) methods with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The purpose of this study was to determine the validity and response of students to learning media based on Macromedia Flash on curved page material. The sample of this research is Singa Putih`s superior MTs students. The research data collection technique used a validation questionnaire from material experts, media experts and student response questionnaires. The choice of this application was based on ease of use and the ability to combine visual, audio-visual and audio-visual resources. The research results were validated by media experts and material experts with a ratio of 86.32% and 82% respectively with the category "Very Valid". The results of the implementation of students using a questionnaire obtained a percentage of 82.8% in the very feasible category.